Involvement of the BDNF gene in loneliness in adolescence: a report of opposite gene effects in boys and girls. - Maaike Verhagen; Eeske van Roekel; Rutger C M E Engels (PLoS ONE, 2014)
Previous research has shown that loneliness has a heritable component and that genes within the serotonin-, dopamine-, and oxytocin systems are related to loneliness in adolescence. In the present study, the relation between the BDNF Val66Met polymorphism and loneliness in adolescent boys and girls was examined in a longitudinal study spanning five annual waves (N = 305). Latent growth curve modeling (LGCM) was used to examine the baseline level and the change in loneliness over time. The main finding was that the BDNF gene was not related to loneliness in the total sample. A BDNF by sex interaction was found, in that Met carrying girls had the highest levels of loneliness at baseline, whereas in boys the ValVal genotype was related to higher levels of loneliness. Our results underline the importance of sex-stratified analyses when examining effects of the BDNF genotype and the necessity of conducting gene studies to intermediate phenotypes of loneliness.